A new way of thinking about IT project management practices: Early empirical results. Issue 1 (2nd January 2017) - Hidding, Gezinus J.; Nicholas, John M.
ABSTRACT: Despite decades of efforts to improve the management of Information Technology (IT) projects, failure rates remain high. This article first reviews literature about information systems success and IT project success. Most of the improvement efforts have focused on advancing variations of the traditional project management paradigm, such as embodied by the Project Management Body of Knowledge. This article describes a new way of thinking about managing IT project called Value-Driven Change Leadership (VDCL), and reports the results of an initial empirical exploration to identify project success factors stemming from VDCL as well as the traditional paradigm. The results are based on data collected from 16 medium-sized IT-intensive projects at eight Chicago-based organizations from six different industries. The results, although not based on a large sample, point to several project management practices associated with project success that stem from both the traditional paradigm as well as VDCL. For example, traditional practices managing stakeholders' expectations, scope, and schedule are associated with project success, as are practices stemming from VDCL, such as managing the end-product's architecture, business value added, and the organization change associated with systems implementation. The results of this study also suggest that further research into new ways of thinking about IT project management may be fruitful.